In-Home Technology Training Among Socially Isolated Older Adults: Findings From the Tech Allies Program. (May 2021) - Fields, Jessica; Cemballi, Anupama Gunshekar; Michalec, Cathy; Uchida, Debbie; Griffiths, Kami; Cardes, Heather; Cuellar, Jacqueline; Chodos, Anna Haseltine; Lyles, Courtney Rees
Technology has the potential to increase social connectedness among older adults, but one-third do not use the internet. We formed a community partnership, Tech Allies, providing tablets, broadband, and 1:1 training to isolated older adults. In a pragmatic pilot trial, participants were randomized into intervention ( n = 44) and waitlist ( n = 39) groups. Volunteers provided eight weekly, in-home iPad lessons. Surveys assessed self-reported loneliness, social support, technology use, and confidence at baseline and follow-up. A subgroup completed in-home interviews. The intervention group showed no change in loneliness, marginally significant improvement in social support and technology confidence, and significant increase in technology use. Among the waitlist group, no changes were observed. Interviews showed some participants felt more connected to the world, and many expressed increased technology confidence. Key implementation lessons on program feasibility are discussed. Embedding training within existing community-based programs holds promise as a potentially sustainable mechanism to provide digital training to older adults.